2023
DOI: 10.3389/fpubh.2023.1051484
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness analysis of 11 treatment paths, seven first-line and three second-line treatments for Chinese patients with advanced wild-type squamous non-small cell lung cancer: A sequential model

Abstract: BackgroundA total of 11 treatment sequences for advanced wild-type squamous non-small cell lung cancer are recommended by Chinese Society of Clinical Oncology Guidelines, consisting of seven first-line and three second-line treatments. Five of these treatments were newly approved in China between 2021 and 2022. We evaluated the effectiveness and cost-effectiveness of these strategies from the Chinese healthcare system perspective.MethodsNetwork meta-analysis with non-proportional hazards was used to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, compared to imported drugs, Chinese ontologic developed inhibitors such as camrelizumab, sintilimab and toripalimab achieve greater accessibility and cost-effectiveness at a lower price while balancing efficacy [ 56 ]. The study included in this review by Zhao et al (2023) also confirmed the cost-effectiveness of camrelizumab in combination with chemotherapy in the treatment of patients with metastatic LSCC [ 55 ]. Similarly, although the amount of supporting evidence is limited, Chen 2022 [ 44 ] also showed that it is not pembrolizumab + chemotherapy that is more cost-effective for Chinese payers, but the locally developed regimen of sintilimab + chemotherapy [ 44 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, compared to imported drugs, Chinese ontologic developed inhibitors such as camrelizumab, sintilimab and toripalimab achieve greater accessibility and cost-effectiveness at a lower price while balancing efficacy [ 56 ]. The study included in this review by Zhao et al (2023) also confirmed the cost-effectiveness of camrelizumab in combination with chemotherapy in the treatment of patients with metastatic LSCC [ 55 ]. Similarly, although the amount of supporting evidence is limited, Chen 2022 [ 44 ] also showed that it is not pembrolizumab + chemotherapy that is more cost-effective for Chinese payers, but the locally developed regimen of sintilimab + chemotherapy [ 44 ].…”
Section: Discussionmentioning
confidence: 62%
“…With ICER below $100,000/QALY as the maximum threshold, the P + C group is cost-effective. Meanwhile, with 2.513 LYs and 1.603 QALYs, Zhao 2023 [ 55 ] demonstrated camrelizumab plus platinum and paclitaxel chemotherapy as most cost-effective first-line choice.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of camrelizumab to chemotherapy was considered cost-effective from a healthcare perspective in China for metastatic NSCLC patients (32). Zhao et al discovered that the combination of camrelizumab with paclitaxel-based chemotherapy, followed by docetaxel, within a selection of 11 treatment sequences for metastatic NSCLC patients, represented a cost-effective treatment option and tislelizumab was deemed the most effective and cost-effective second-line option (33). The combination of sintilimab and chemotherapy was proven to be more costeffective than the combination of pembrolizumab and chemotherapy for patients with metastatic NSCLC in China, as the QALYs obtained in the sintilimab group were similar to those in the pembrolizumab group, with substantially lower costs (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies ( 10 14 ) have demonstrated that economic evaluations of imported PD-1/PD-L1 inhibitors, such as pembrolizumab, nivolumab, and atezolizumab, do not confer a cost-effectiveness advantage. As a domestically developed PD-1/PD-L1 inhibitor, tislelizumab offers a lower price compared to imported counterparts while maintaining comparable efficacy ( 12 ). Consequently, the CSCO guidelines advocate for tislelizumab as second-line treatment in patients with driver-negative advanced or metastatic NSCLC.…”
Section: Introductionmentioning
confidence: 99%